HUBUNGAN SIMBOL CATCALLING TERHADAP ANXIETY MAHASISWI FAKULTAS USHULUDDIN ADAB DAN DAKWAH - Rini Puti Intan Suri; Zafirah Quroatun 'Uyun (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The main problem in this thesis is that relationship catcalling symbol to female student anxiety of Ushuluddin Adab And Da'wah Faculty. The aim of this research is to find out significance level of relationship between catcalling symbol to female student anxiety of Ushuluddin Adab And Da'wah Faculty. The theory used in this research is symbolic interactionism and anxiety, uses a quantitative research methodology with a correlation approach using the product moment correlation significance test comparing rCount with rTable. The data collection technique that the researcher used was through distributing questionnaires to female students from 2021 generation, 2022 generation, 2023 generation Faculty of Ushuluddin Adab and Da'wah with a sampel size of 85 respondents.. The result is that there is a very weak relationship between the catcalling symbol variable and anxiety, where the results obtained from the product moment correlation test obtained a coefficient value of 0.020, indicating a very low relationship value. This means that catcalling symbol does not have a significant relationship with anxiety, however, both variables still have a very weak relationship coefficient. The coefficient of determination (R Square) value is 1.3%, this shows that the relationship between catcalling symbol and anxiety among female students of Ushuluddin Adab And Da'wah Faculty is 1.3%, while 98.7% is influenced by other variables. Keywords : Anxiety, Catcalling Symbol, Symbolic Interaction Theory